Sarcopenia and Androgens: A Link between Pathology and Treatment - Basualto-Alarcón, Carla; Varela, Diego; Duran, Javier; Maass, Rodrigo; Estrada, Manuel (Frontiers in Endocrinology, 2014)
Sarcopenia, the age-related loss of skeletal muscle mass and function, is becoming more prevalent as the lifespan continues to increase in most populations. As sarcopenia is highly disabling, being associated with increased risk of dependence, falls, fractures, weakness, disability, and death, development of approaches to its prevention and treatment are required. Androgens are the main physiologic anabolic steroid hormones and normal testosterone levels are necessary for a range of developmental and biological processes, including maintenance of muscle mass. Testosterone concentrations decline as age increase, suggesting that low plasma testosterone levels can cause or accelerate muscle- and age-related diseases, as sarcopenia. Currently, there is increasing interest on the anabolic properties of testosterone for therapeutic use in muscle diseases including sarcopenia. However, the pathophysiological mechanisms underlying this muscle syndrome and its relationship with plasma level of androgens are not completely understood. This review discusses the recent findings regarding sarcopenia, the intrinsic and extrinsic mechanisms involved in the onset and progression of this disease and the treatment approaches that have been developed based on testosterone deficiency and their implications.